2021
DOI: 10.1089/bfm.2020.0314
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Breastfeeding Equity and Justice in Black Communities: Past, Present, and Future

Abstract: Background: Breastfeeding is protective of maternal and infant health across the life course. Increasing breastfeeding rates in Black communities is an important public health strategy to address maternal and infant mortality and morbidity. Methods: Data trends for the past 10 years suggest that Black-led community efforts; local, state, and national initiatives; and maternity care practices that are supportive of breastfeeding have been effective in improving and increasing breastfeeding rates among Black wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 36 publications
(64 reference statements)
2
34
0
Order By: Relevance
“…Recognition of healthcare service differences and perceptions must be further studied to understand how to achieve equitable care versus equal care. To accomplish this, Asiodu and colleagues (2021) recommend racially diverse research teams and listening to the perspectives of Black women, families, and communities. In a recent report, researchers found that hospitals can both implement evidence-based perinatal care policies and strengthen practices to specifically reduce disparities in breastfeeding initiation rates (Chiang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Recognition of healthcare service differences and perceptions must be further studied to understand how to achieve equitable care versus equal care. To accomplish this, Asiodu and colleagues (2021) recommend racially diverse research teams and listening to the perspectives of Black women, families, and communities. In a recent report, researchers found that hospitals can both implement evidence-based perinatal care policies and strengthen practices to specifically reduce disparities in breastfeeding initiation rates (Chiang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Systemic and structural barriers such as racism and inequitable access to maternity care practices supportive of breastfeeding further perpetuate human milk feeding inequities in Black communities. 18 Online discussions on this topic have been centered at the individual level, instead of community or systems levels. The calls to "just breastfeed" as an easy and quick solution to the infant formula shortage are harmful.…”
Section: Disclosurementioning
confidence: 99%
“…The World Health Organization recommends exclusive breastfeeding for the first six months after birth, and up to two years with the introduction of complementary foods (9). Unfortunately, due to systemic and structural barriers such as racism, lack of workplace accommodations, and inequitable access to human milk feeding resources, breastfeeding disparities and inequities remain (10)(11)(12). In general, breastfeeding initiation and duration rates are higher among Asian and White mothers and lower among Black and Indigenous mothers in the U.S (13).…”
Section: Introductionmentioning
confidence: 99%